A tuber vegetation harvester - Ahmad, Desa; Kakahy, Amer Najat Najmaldeen; Hamid, Md. Akhir; Sulaiman, Shamsuddin; Arif, Ishak (2013)
The present invention relates to a tuber vegetation harvester comprising: a digging-harvesting mechanism (16) to dig and harvest tuber from soil including: a chasis as a main frame (1); a pair of coulter discs (15) fixed at the chasis (1) to cut leaves on both sides of the ridges; a digger blade (17) adjacent to the pair of coulter discs (15) to cut the soil and to lift the tubers onto a separating unit; hydraulic hose and lever controller (18); and rear wheels (20) characterized in that a cutting and pulverizing mechanism is incorporated before the digging-harvesting mechanism (16). The present invention which combines both the cutting and digging in a single operation provides significant reduction in the time taken for harvesting, the fuel consumption and the number of machines used which gives some economical advantages.